Marketing Ethics and Competitiveness: an Empirical Study of Small and Medium Sized Enterprises (SMEs) in Algeria (مجلة إضافات إقتصادية, 2021)
In recent years, business ethics (honesty, responsibility, fairness, respect, transparency, citizenship) have gained great importance inmarketing practices, as ethics programs can be profitable and help buildlong-term marketing relationships. The main purpose of this study is toexamine the influence of applying marketing ethics on competitivenessamong the small and medium sized enterprises (SMEs) in Algeria. Toachieve this goal, a questionnaire was administered to a sample of (431)managers of SMEs, using the SPSS program to ensure the statisticalanalysis of the data.The results have shown the presence of a statisticallysignificant influence of marketing ethics on the competitiveness of theAlgerian SMEs. Keywords: marketing; ethics; values; small and medium sized enterprises(SMEs); competitiveness. Jel Classification Codes: M14, M30, M31, M37